Flood early warning systems for landlocked countries: A study in Chikwawa District in Malawi - Maulana, Precious; Karuniasa, Mahawan; Sodri, Ahyahudin (Center for Science and Technology, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study addresses a critical gap in the understanding of Flood Early Warning Systems (FEWS) within landlocked, resource-constrained contexts by focusing on Chikwawa District, Malawi. The study moved beyond descriptive accounts to provide a nuanced analysis grounding the inquiry into disaster risk reduction theory to assess both the operational and community-level effectiveness of current systems. Employing a mixed-methods approach, this research combines quantitative data from 204 household surveys with qualitative insights from four key informant interviews to triangulate the assessment of flood preparedness, warning dissemination, and community response capabilities. The findings reveal that, while national agencies have established relatively robust monitoring frameworks, significant challenges persist in the final-mile communication loop, resulting in a notable disparity between warning issuance and effective community action. Specifically, issues such as a lack of trust in official messages, inconsistent communication channels, and the absence of well-defined evacuation routes critically hinder the system's overall efficacy. By integrating geographical analysis with on-the-ground perspectives, this paper provides a more complete picture of the obstacles to effective FEWS. The study's key policy implications include the need for more localised and tailored communication strategies, community-based drills to foster trust, and targeted infrastructure investments to enhance last-mile delivery and response capabilities. This work contributes to academic literature by offering a theoretically grounded case study from a landlocked perspective, enriching the global discourse on flood resilience.